ANALISIS PENGARUH BAURAN PROMOSI TERHADAP KEPUTUSAN MAHASISWA MEMILIH AKADEMI PARIWISATA INDONESIA - Sulih Wahyudiono (LPPM Universitas Asa Indonesia, 2015)
The influence of promotion mix toward the students decision for choosing (AKPINDO) Jakarta The problem of the research is how about the advertising, sales promotion and direct marketing toward the students decision for choosing AKPINDO Jakarta. This researh aims to know (1) the advertising, sales promotion and direct marketing influencing students decision in choosing at AKPINDO Jakarta (2) to know which be the most dominant factor to the student decision. The sample of this research was 58 (fifty eight) respondens. The research type was descriptive research supported by survey method, quantitative descriptive research approach, the variables measured with rating scale. The processing of data supported divice SPSS version 17.0 with descriptive analysis and hypothesis test uses multiple linier regression analysis. The result of research indicate that promotion mix (advertising, sales promotion and direct marketing ) about high significan toward the students decision for choosing AKPINDO Jakarta. And the most dominant factor is sales promotion that influencing students decision to studying at AKPINDO Jakarta.